Local government and civic society in small states (Commonwealth Local Government Forum LondonGB, 1999)
Presents the Malta Declaration on Local Government and Civic Society in Small and Island Developing States as well as the summary of symposium deliberations.
Keywords: LOCAL GOVERNMENT